Enhanced mechanical and thermal properties of hybrid SnO2–woven carbon fiber composites using the facile controlled growth method. (14th September 2016) - Kong, Kyungil; Kwon, Obum; Park, Hyung Wook
Abstract: Tin oxide (SnO2 ) nanorods (NRs) were successfully grown using a two-step seed-mediated hydrothermal method in the absence of surfactants. The enhanced mechanical properties of the impact absorbed energy (71.65%), ultimate tensile strength (35.07%), in-plane shear strength (49.07%) and elastic modulus (44.15%) were obtained for 70 mM of SnO2 –woven carbon fiber (WCF) composites. The higher electrical resistive heating in the interlaminar region of electrified SnO2 (70 mM)–WCF composite sheets was observed at 108.92% improvement of an average temperature under an applied current of 3 A for 20 min. It was attributed to the fact that a higher SnO2 NR content provided secondary reinforcement and subsidiary electrified heat traps by modifying the interphase region between the CFs and polymers. X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) were used to examine the morphology and phase structure of one-dimensional (1D) grown SnO2 NR arrays. The crystalline 1D SnO2 nanostructure evolved via a self-assembly mechanism that depended on nuclei of Sn 4+ /OH − ions in a supersaturated solution at a pH of about 13. This facile controlled growth of SnO2 embedded in CF composites is relevant to engineering applications requiring higher mechanical performance and thermal heating than attainable with conventional CF-reinforced polymer composites.